The Implications of The Role of Political Parties in Strengthening Democracy in Indonesian Legislative Elections - Afrizal Afrizal; Tamaulina Br. Sembiring (Prosiding Seminar Nasional Ilmu Hukum, 2025)
Rapid developments in information technology have opened up opportunities for new threats to national security, one of which is hacking of information systems. Cyber attacks not only cause economic losses and disrupt public services, but also pose a serious threat to Indonesia's digital sovereignty. In this context, state intelligence has a strategic role as the front line in detecting, analyzing, and countering various forms of threats to the country's strategic information systems. However, strengthening the function of state intelligence in dealing with hacking crimes still faces various obstacles, ranging from regulatory aspects that are not yet adaptive, weak inter-agency coordination, to limitations in technology and human resources. This study aims to examine the extent of the effectiveness of strengthening state intelligence in countering information system hacking, as well as to formulate the urgency of updating national legal policies that support the formation of a strong, integrated, and professional cyber intelligence system. Using a normative legal research method supported by a conceptual and case approach, this study concludes that strengthening state intelligence requires regulatory reform, institutional integration, and investment in technology and human resources in order to maintain national sovereignty in the digital age.